Pigs with an INS point mutation derived from zygotes electroporated with CRISPR/Cas9 and ssODN - Tanihara, Fuminori; Hirata, Maki; Namula, Zhao; Do, Lanh Thi Kim; Yoshimura, Naoaki; Lin, Qingyi; Takebayashi, Koki; Sakuma, Tetsushi; Yamamoto, Takashi; Otoi, Takeshige (Frontiers in Cell and Developmental Biology, 2023)
Just one amino acid at the carboxy-terminus of the B chain distinguishes human insulin from porcine insulin. By introducing a precise point mutation into the porcine insulin (INS) gene, we were able to generate genetically modified pigs that secreted human insulin; these pigs may be suitable donors for islet xenotransplantation. The electroporation of the CRISPR/Cas9 gene-editing system into zygotes is frequently used to establish genetically modified rodents, as it requires less time and no micromanipulation. However, electroporation has not been used to generate point-mutated pigs yet. In the present study, we introduced a point mutation into porcine zygotes via electroporation using the CRISPR/Cas9 system to generate INS point-mutated pigs as suitable islet donors. We first optimized the efficiency of introducing point mutations by evaluating the effect of Scr7 and the homology arm length of ssODN on improving homology-directed repair-mediated gene modification. Subsequently, we prepared electroporated zygotes under optimized conditions and transferred them to recipient gilts. Two recipients became pregnant and delivered five piglets. Three of the five piglets carried only the biallelic frame-shift mutation in the INS gene, whereas the other two successfully carried the desired point mutation. One of the two pigs mated with a WT boar, and this desired point mutation was successfully inherited in the next F1 generation. In conclusion, we successfully established genetically engineered pigs with the desired point mutation via electroporation-mediated introduction of the CRISPR/Cas9 system into zygotes, thereby avoiding the time-consuming and complicated micromanipulation method.